1995
DOI: 10.1093/oxfordjournals.humrep.a135837
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and biochemistry of in-vitro produced bovine embryos: implications for their cryopreservation

Abstract: Examination of some ultrastructural and physiological characteristics of in-vitro produced bovine embryos may help to explain why such embryos are more sensitive to freezing than their in-vivo derived counterparts. Improvement of embryo survival after freezing can be achieved by changing the conditions of their culture, selection of embryos based on the kinetics of their development, and changing "standard' freezing procedures. Cryopreservation of embryos by vitrification, in particular, seems to yield higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
70
0
6

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(82 citation statements)
references
References 0 publications
6
70
0
6
Order By: Relevance
“…However, in vitro produced (IVP) embryos are more sensitive to chilling (31) and freezing than their in vivo countea'parts (16,20). The differences between in vitro and in vivo produced embryos have been investigated by several authors (13,36).…”
Section: ~Troductionmentioning
confidence: 99%
“…However, in vitro produced (IVP) embryos are more sensitive to chilling (31) and freezing than their in vivo countea'parts (16,20). The differences between in vitro and in vivo produced embryos have been investigated by several authors (13,36).…”
Section: ~Troductionmentioning
confidence: 99%
“…Improvement of embryo survival after freezing can be achieved by changing the conditions of in vitro culture, and/or modifying ''standard'' cryopreservation procedures [14].…”
Section: Introductionmentioning
confidence: 99%
“…Slow freezing of in vitro produced embryos reduced post thaw survival rates compared with their in vivo counterparts, mostly due to their susceptibility to ice crystal formation. Cryopreservation of embryos by vitrification yields higher survival than conventional slow freezing [14,[29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…This could be related to the embryo density in the culture medium since good results were reported culturing one embryo per pL of medium under mineral oil (Ferry et al, 1994 (Ferry et al, 1994;Massip et al, 1995).…”
mentioning
confidence: 99%
“…Recently, it was demonstrated that the production of bovine blastocysts was also possible in a simple defined medium like SOF, although the concentration of O Z (5%) is critical since a reduced embryo development at high oxygen concentration is observed (Carolan et al, 1995;Massip et al, 1995). The low oxygen tension is thought to act by reducing auto-oxidative damage to which the embryos are susceptible.…”
mentioning
confidence: 99%